2021
DOI: 10.1177/10760296211039287
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation Serum miR-19a-3p is a Diagnostic Biomarker for Asymptomatic Carotid Artery Stenosis and a Promising Predictor of Cerebral Ischemia Events

Abstract: This study aims to identify the diagnostic potential of microRNA-19a-3p (miR-19a-3p) for asymptomatic carotid artery stenosis (CAS) and clinical predictive potential for cerebral ischemia events (CIEs). Serum samples from 101 asymptomatic CAS patients and 98 healthy controls were collected. And it was found that serum miR-19a-3p in asymptomatic CAS patients was generally elevated ( P < .05). Increased miR-19a-3p in asymptomatic CAS was associated with severe CAS (odds ratio  = 3.920, 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Similar results were observed for miR-19a-3p by Liu et al who stated that higher expression of serum miR-19a-3p (HR = 8.507, 95% CI = 2.239–32.328, p = 0.002) and degree of ICAS (HR = 3.695, 95% CI = 1.127–12.109, p = 0.031) were independent predictors for the onset of IS [ 130 ], whereas Lu et al found miR-27b an important risk factor of IS (HR = 5.067, 95% CI = 1.170–21.943, p = 0 .030) [ 131 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...supporting
confidence: 85%
“…Similar results were observed for miR-19a-3p by Liu et al who stated that higher expression of serum miR-19a-3p (HR = 8.507, 95% CI = 2.239–32.328, p = 0.002) and degree of ICAS (HR = 3.695, 95% CI = 1.127–12.109, p = 0.031) were independent predictors for the onset of IS [ 130 ], whereas Lu et al found miR-27b an important risk factor of IS (HR = 5.067, 95% CI = 1.170–21.943, p = 0 .030) [ 131 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...supporting
confidence: 85%
“…To support our findings, predictive role of miR-19a in future cerebral ischemic events occurrence was observed in patients with asymptomatic carotid artery stenosis (CAS), and miR-19a-3p expression was markedly higher than that in healthy subjects. Moreover, miR-19a-3p was a strong predictor of the severity of CAS [45]. Based on in vitro and in vivo analysis it was shown that miR-19a-3p directly targets and inhibits expression of IGFBP3, the gene encoding one of the insulin-like growth factors, and thus induce inflammation and apoptosis processes related to ischemia/reperfusion brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…miR-22-3p can regulate human artery vascular smooth muscle cell proliferation and migration by targeting HMGB1, and may be therapeutic targets in the treatment of human arteriosclerosis obliterans 32) . Dysregulation Serum miR-19a-3p is a Diagnostic Biomarker for Asymptomatic Carotid Artery Stenosis and a Promising Predictor of Cerebral Ischemia Events 33) . miR-320b is a speci c serum marker for carotid atherosclerosis and vulnerable plaque, which can be used to assist in the diagnosis of cerebrovascular diseases 34) .…”
Section: Discussionmentioning
confidence: 99%